PENINGKATAN HASIL BELAJAR SERVICE BOLA VOLI MELALUI EVALUASI PEMBELAJARAN MENGGUNAKAN MEDIA AUDIOVISUAL DAN MODIFIKASI BOLA SISWA KELAS X SMK NEGERI 5 MEDAN - Iwan Saputra; Hendra Maulana (Universitas Negeri Medan, 2019)
The purpose of this study is to improve learning outcomes under volleyball service through evaluation using audiovisual media and ball modification in class X students of SMK Negeri 5 Medan. When the study was conducted in May 2019, the sample in this study was 26 students, consisting of 16 sons and 10 daughters. This research method is classroom action research (CAR). Judging from the preliminary data under the volleyball service, only 9 students completed (35%) and 17 students did not complete (65%). After the cycle I action, 17 students (65.4%) and 9 students (34.6%) had not yet completed classically. Then in cycle II students who completed 23 people (88.5%) and students who did not complete 3 people (11.5%). The percentage of students 'mastery learning in the initial data was 35%, in the first cycle test increased to 65.4%, and in the second cycle the percentage of students' mastery learning had reached 88.5%. Based on the results of data analysis, it can be concluded that through the evaluation of learning using audio visual media and ball modification can provide improved learning outcomes under the volleyball service in class X students of SMK Negeri 5 Medan in the 2018/2019 school year.